A tool to optimise dairy herd replacements combining conventional, sexed, and beef semen - Valentina Ferrari; Maurizio Marusi; Mauro Penasa; Johannes Baptist Cornelis Henricus Maria van Kaam; Raffaella Finocchiaro; Martino Cassandro (Italian Journal of Animal Science)
A tool to help Italian dairy farmers choosing the most suitable replacement strategy has been developed. The approach aimed to identify yearly female replacement needs based on herd performance level and combination of different semen type (conventional, sex-sorted, and beef semen), with the ultimate goal of enhancing farm profit. A case study based on a 350-cow Holstein herd was used and three levels of herd fertility (high, medium, and low) were simulated to define the yearly number of dairy female replacements needed and the number of females yielded under different semen utilisation scenario. The number of annual dairy replacements was obtained as the number of cows multiplied by the replacement rate and adjusted by the age at first calving. Number of animals yielded was used to evaluate the replacement cost per 100 L of milk. Then, four strategies of sexed semen utilisation were combined with five strategies of beef semen use. Animals that were not inseminated with sexed or beef semen were bred with conventional semen. Regardless of fertility level, the number of dairy female replacement heifers that the farm needs are 110. Increasing beef semen use allows farmer to yield less replacement heifers. Furthermore, as beef semen use increases and the number of replacement heifers decreases, replacement cost per 100 L of milk reduces. Therefore, our results highlighted that replacement costs increase with increasing number of yielded heifers. Hence, combining beef and sexed semen to reach heifer balance close to zero, decreased the replacement cost.